EFFECTIVENESS OF ASSERTIVENESS TRAINING IN GROUP COUNSELING TO REDUCE PEOPLE-PLEASING BEHAVIOR AMONG STUDENTS IN SURABAYA - Arlenia, Mellbi Ansiska; Farid, Dimas Ardika Miftah (Jurnal Bikotetik (Bimbingan dan Konseling: Teori dan Praktik), 2025)
This research aims to determine the effectiveness of assertive training techniques in group counseling in reducing people pleasing among students in the city of Surabaya. This research uses a quantitative research design one grup pre-test post-test design. The population of this research are active students in the city of Surabaya who have attitudes people pleasing. The sample consisted of five students who were indicated to have attitudes people pleasing quite high and medium. The results show that there has been a decline people pleasing to students after conducting a counseling session and given treatment using assertive training techniques. This research uses tests Wilcoxon to analyze the data, and on this data shows Asymp. Say. (2-tailed) is worth 0.042. It is known that the value of 0.042 is smaller than 0.05, meaning that Ha is accepted and H0 is rejected. It can be interpreted that assertive training is effective in reducing attitudes people pleasing to students in the city of Surabaya